2015
DOI: 10.1007/s10853-015-8871-x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia borane confined by poly(methyl methacrylate)/multiwall carbon nanotube nanofiber composite, as a polymeric hydrogen storage material

Abstract: In this work, poly(methyl methacrylate)/ammonia borane/multiwall carbon nanotube (PMMA/AB/ MWCNT) nanofiber composites have been fabricated and the synergetic nanoconfinement effect of nanofiber and CNT components on dehydrogenation temperature and liberating unwanted byproducts of AB (NH 3 BH 3 ) have been studied. The results of dehydrogenation of PMMA/AB and PMMA/ AB/MWCNT samples show 112 and 85°C exothermic reaction temperatures, which are dramatically lower than pure AB (120°C). Furthermore, by capture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Polymer composites are a particularly attractive option to implement these approaches, since polymers can be cheap and lightweight. To date, polyIJmethyl acrylate), 22 polyIJmethyl methacrylate), 23 polyIJvinyl pyrrolidone) 24 and polyacrylamide 25 composites have been successfully produced with AB. These materials combine confinement effects and chemical interactions between AB and oxygen-containing functional groups within the polymer to improve the properties of the hydrogen storage material.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites are a particularly attractive option to implement these approaches, since polymers can be cheap and lightweight. To date, polyIJmethyl acrylate), 22 polyIJmethyl methacrylate), 23 polyIJvinyl pyrrolidone) 24 and polyacrylamide 25 composites have been successfully produced with AB. These materials combine confinement effects and chemical interactions between AB and oxygen-containing functional groups within the polymer to improve the properties of the hydrogen storage material.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, despite these merits, there are technical barriers preventing AB to be practically used as an on-board energy source, such as its slow thermal kinetics below 100 C and unwanted by-products including ammonia (NH 3 ), diborane (B 2 H 6 ), and borazine (B 3 H 6 N 3 ), which will poison the catalyst in a proton membrane fuel cell. 2,3,[6][7][8] To date, a number of ways have been investigated to tackle the above mentioned issues including the use of metal catalysts 3,[9][10][11][12][13][14][15][16][17] or metal-free catalysts, [18][19][20] the formation of metal hydrides, [21][22][23] the realisation of metal or methane substitution, [24][25][26] the utilisation of ionic liquid, 27,28 additives, 29,30 or nanoconfinement 8,[31][32][33][34][35][36][37][38][39][40] etc. Significant improvements on lowering the hydrogen release temperatures, improving the kinetics and avoiding the emissions of those harmful by-products have been made.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] The first report on nanoconfinement of AB in mesoporous silica demonstrated a lower dehydrogenation temperature, suppression of borazine release, and lower enthalpy of the decomposition, 31 which has triggered a number of studies in this area. Nanoscaffolds including mesoporous silica, 31,[45][46][47] mesoporous carbon, 32,38,48,49 activated carbon, 50 carbon nanotubes, 39,40 metal-organic frameworks (MOFs), 8, 33, 36, 37, 51-53 porous MnO 2 35 and low-density porous aromatic framework 34 have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations have been previously reported by Li et al 26 where blending of PAM was performed with AB, and a reduced dehydrogenation temperature was observed due to the interaction between CO, NH 2 of the polymer, and the AB molecule. Alipour et al 51 reported fabrication of poly(methyl methacrylate)/ammonia borane/multiwall carbon nanotube (PMMA/AB/MWCNT) nanofiber composites for studying the dehydrogenation behavior of AB in these composites. It was observed that the interaction between the oxygen group from the carbonyl group of PMMA and the boron from AB led to formation of B−O bonds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%